The translation of Madurese cultural expressions into English - Masduki, Masduki (citeus, 2016)
This article reports on research project analyzing the specific terms of cultural expressions that exist in Madura Island, the strategies in translating Madurese cultural expressions into English, andhow the strategies of transferring messages take place. The sources of data utilized in this study were the translators in the local government, private sectors, educational institutions, and both official and unofficial documents throughout the region containing Madurese cultural expressions. The data were collected using document analysis, questionnaire distribution, and in-depth interviews. The analysis was carried out in view of interactive model. The findings show that categories of specific terms found in the Madurese cultural expressions include: culture of materials (33.06%), ecological terms (19.35%), and socio-culture (47.58%). In addition, the strategies of translation applied to solve the challenge of translation include: adaptation (25.81%), calque (3.22%), modulation (4.84%), borrowing (4.03%), descriptive equivalence (51.61%), and a superordinate-subordinate scope (10.48%). The strategies and the quality of translation have some potential for the development of culture-based translation.